Fibrosis and cancer: shared features and mechanisms suggest common targeted therapeutic approaches. Issue 6 (5th December 2020) - Landolt, Lea; Spagnoli, Giulio C; Hertig, Alexandre; Brocheriou, Isabelle; Marti, Hans-Peter
Abstract: Epidemiological studies support a strong link between organ fibrosis and epithelial cancers. Moreover, clinical and experimental investigations consistently indicate that these diseases intertwine and share strikingly overlapping features. As a deregulated response to injury occurring in all body tissues, fibrosis is characterized by activation of fibroblasts and immune cells, contributing to progressive deposition of extracellular matrix (ECM) and inflammation. Cancers are driven by genetic alterations resulting in dysregulated cell survival, proliferation and dissemination. However, non-cancerous components of tumour tissues including fibroblasts, inflammatory cells and ECM play key roles in oncogenesis and cancer progression by providing a pro-mutagenic environment where cancer cells can develop, favouring their survival, expansion and invasiveness. Additional commonalities of fibrosis and cancer are also represented by overproduction of growth factors, like transforming growth factor β, epithelial-to-mesenchymal transition, high oxidative stress, Hippo pathway dysfunctions and enhanced cellular senescence. Here, we review advances in the analysis of cellular and molecular mechanisms involved in the pathogenesis of both organ fibrosis and cancer, with particular reference to chronic kidney diseases and renal cell cancers. Most importantly, improved understanding of common features is contributing to the development of innovative treatment strategies targeting shared mechanisms.